POLA KOMUNIKASI EFEKTIF DALAM MODERASI BERAGAMA : MEMBANGUN DIALOG HARMONIS - Muhamad Nurul Fajri (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2023)
Effective communication patterns play a crucial role in indicators of religious moderation in a multicultural and pluralist society. This study aims to analyze the factors that influence communication patterns in the context of indicators of religious moderation and the resulting implications. The research method used is literature study with in-depth text analysis. The research findings indicate that factors such as the use of inclusive and non-discriminatory language, accurate understanding of different religions, active listening, empathy, collaboration between individuals or groups with different religious beliefs, and social and cultural contexts influence communication patterns in indicator of religious moderation. Effective communication patterns can help prevent conflict, promote mutual understanding, and build harmonious dialogue between individuals or groups with different religious beliefs. The implications of effective communication patterns in religious moderation indicators include harmonious relationships between individuals, cross-cultural cooperation, and inclusive community development. Awareness of the importance of inclusive and non-discriminatory language as well as an accurate understanding of different religions is the key to promoting effective communication patterns. Effective communication patterns in religious moderation indicators contribute to the creation of harmonious relationships, deeper mutual understanding, and inclusive cooperation in a multicultural and pluralist society. Keywords: communication patterns, religious moderation, inclusiveness, non-discrimination, understanding, active listening, empathy, collaboration, social context, culture, multicultural society.